Práticas de leitura na estação Cabo Branco: análise os projetos de incentivo à leitura da instituição sob a visão dos seus coordenadores - LOPES, Maria Alves (2015)
There are many reading concepts, we know that, but our perception is what makes us readers from the moment that we are born and since we open our eyes to the world, for life. We read everything around us, the environment we live in and grow into, until we finally get to the point where we start decoding codes, connecting and coming up with words. It‟s in that moment that we also become readers of the written words. And the reading habit, encouraged by actions taken by the various projects, can develop reasoning, critical thinking and the ability of interpretation. Considering those facts, this study is the result of a research that had the analysis of the reading of projects that are offered to the community by Estação Cabo Branco from the perspective of its coordinators, to encourage the habit of reading, as its main goal. This descriptive and qualitative research included a field survey and a questionnaire composed of open questions, which was the instrument used to collect the data. The questionnaire was applied among the coordinators of the three reading projects that were developed in the institution: Contação de história, Troca de livro e conhecimento e Roda de leitura. The survey results show that the reading projects can be seen as valid activities to encourage and to promote the reading habit, and that these projects can also be developed and applied in many different ways. Although they have similar goals, each of the analyzed projects have their own peculiarities: the "Contação de história" can use story books or not, representing and making the public travel through reading, listening to the stories or living the characters‟ experiences; The "Troca de livro e conhecimento" helps to enrich and disseminate the knowledge of those who can‟t buy new books all the time through their collections, available for exchange or even donation; the project "Roda de leitura" does a little more, it brings the reader and the author together so that both sides have the chance to know the other and complement each other. The reader discovers the person behind the written words and that can even possibly encourage the appearance of new authors. We can conclude that the reading projects developed in Estação Cabo Branco not only promote reading as something pleasurable and fun but also establish informational practices that contribute to the awareness of critical thinking citizens who can change things for better on a personal and a collective level as well.